2011
DOI: 10.6001/biologija.v57i2.1835
|View full text |Cite
|
Sign up to set email alerts
|

IAA production and other plant growth promoting traits of endophytic bacteria from apple tree

Abstract: All plants in nature harbor a diverse community of endophytic bacteria. They can produce a wide range of various compounds, which can positively affect the host plant growth. Endophytes can participate in providing plant with nutrients, competing with plants pathogens or directly effecting the plant growth by synthesis of phytohormones.In this study, endophytic bacteria associated with apple tree buds were isolated, characterized and tested for their ability to produce the plant hormone IAA (indole 3 acetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
(9 reference statements)
0
9
0
3
Order By: Relevance
“…Zat pengatur tumbuh terutama asam indol asetat (AIA) seringkali berpengaruh terhadap pertumbuhan akar primer, akar sekunder, dan rambut akar [10] sehingga AIA merupakan auksin alami yang memegang peranan penting dalam peningkatan pertumbuhan tanaman [11]. MILIŪTĖ dan BUZAITĖ melaporkan bahwa endofit yang diisolasi selain mampu mengikat nitrogen, juga menghasilkan AIA dan melarutkan fosfat [12]. Secara sistematis, bakteri endofit membentuk koloni dan mempengaruhi pertumbuhan tanaman melalui perlindungan terhadap hama penyakit, degradasi kontaminan, dan sekresi hormon tumbuh [13,14].…”
Section: Pendahuluanunclassified
“…Zat pengatur tumbuh terutama asam indol asetat (AIA) seringkali berpengaruh terhadap pertumbuhan akar primer, akar sekunder, dan rambut akar [10] sehingga AIA merupakan auksin alami yang memegang peranan penting dalam peningkatan pertumbuhan tanaman [11]. MILIŪTĖ dan BUZAITĖ melaporkan bahwa endofit yang diisolasi selain mampu mengikat nitrogen, juga menghasilkan AIA dan melarutkan fosfat [12]. Secara sistematis, bakteri endofit membentuk koloni dan mempengaruhi pertumbuhan tanaman melalui perlindungan terhadap hama penyakit, degradasi kontaminan, dan sekresi hormon tumbuh [13,14].…”
Section: Pendahuluanunclassified
“…Bakteri endofit selain menghasilkan fitohormon dan pengikat N (MILIŪTĖ dan BUZAITĖ, 2011;SHI et al, 2009), serta sebagai pertanahanan tanaman QUECINE et al, 2012). Selain itu juga memberikan sumbangan hara lain diberikan oleh bakteri endofit diduga melalui proses mineralisasi antara lain P, K, Ca, dan Mg serta unsur-unsur mikro seperti Fe.…”
Section: Produksi Bahan Keringunclassified
“…Thamizhvendan et al, (2010) isolated 12 endophytic bacteria which were reported to synthesize significant amount of IAA in nutrient broth provided with tryptophan as precursor. Miliūtė and Buzaitė (2011) were isolated endophytic bacteria from the apple tree buds and investigated their role in production of plant hormone IAA. They reported that nine isolates were able to produce IAA with concentration varied between 0.12-0.24 micrograms per milligram of protein in culture.…”
Section: Production Of Plant Growth Regulators (Pgr)mentioning
confidence: 99%